Expression of human and mouse nonhistone chromosomal proteins in hybrid mouse erythroleukemia cells containing a single human chromosome. - Bode, U (1981)
The nonhistone chromosomal proteins of a series of hybrid mouse erythroleukemia cell lines containing human chromosome 16 were investigated by two-dimensional gel electrophoresis to determine if such cells contained nonhistone chromosomal proteins of both human and mouse origin. Comparison of the two-dimensional gel electrophoretograms of the nonhistone chromosomal proteins of mouse and human cell lines showed 400 and 280 chromosomal proteins, respectively, of which about 75% were electrophoretically identical. The two-dimensional gel electrophoretogram of a cloned hybrid mouse erythroleukemia cell line that retained a tetraploid complement of mouse chromosomes and human chromosome 16 (as the only human chromosome) displayed a nonhistone chromosomal protein of pI 6.2 and Mr 65,000. This protein, which comigrates with a nonhistone chromosomal protein present in the human cell line used to produce this hybrid cell and which is also present in two additional human cells lines studied, could not be detected in the mouse erythroleukemia parent before fusion. This polypeptide also was shown by similar techniques to be associated with the presence of human chromosome 16 in four out of five other independently derived hybrid mouse erythroleukemia cell lines that contained a near tetraploid complement of mouse erythroleukemia chromosomes.